Effect of seeding systems and application rates of mineral and organic fertilizers on stem height of sunflower (Texas Journal of Agriculture and Biological Sciences, 2025)
This article examines the effect of sowing scheme, organic and biohumus fertilizers on the germination of sunflower seeds and seedling density. The highest germination rate was observed when organic fertilizers were applied at a rate of 20 tons per hectare, and the seeds were 70x20-1; 70x25-1; When studying the 4-5-6 variants planted in 70x30-1 systems and applying 10-15-20 tons of manure per hectare in addition to the mineral fertilizers N150P105K150 kg/ha during the growth period, the stem height was 17.0-19.0-20.5 cm in the 1st pair of leaves formation phase, 38.3-41.3-44.5 cm in the 3rd pair of leaves formation phase, 64.7-69.4-74.0 cm in the basket formation phase, 96.1-102.8-108.9 cm in the flowering phase, 119.4-129.1-138.4 cm in the seed setting phase, and 134.0-148.7-162.7 cm in the full ripening phase, and the seeds 70x20-1; 70x25-1; 70x30-1 systems were planted, and mineral fertilizers were applied at the rate of N150P105K150 kg/ha during the growing season.